2010
DOI: 10.1111/j.1365-2958.2010.07273.x
|View full text |Cite
|
Sign up to set email alerts
|

CtpV: a putative copper exporter required for full virulence of Mycobacterium tuberculosis

Abstract: SummaryCopper is a required micronutrient that is also toxic at excess concentrations. Currently, little is known about the role of copper in interactions between bacterial pathogens and their human hosts. In this study, we elucidate a mechanism for copper homeostasis in the human pathogen Mycobacterium tuberculosis via characterization of a putative copper exporter, CtpV. CtpV was shown to be required by M. tuberculosis to maintain resistance to copper toxicity. Furthermore, the deletion of ctpV resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
214
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(232 citation statements)
references
References 43 publications
7
214
0
11
Order By: Relevance
“…However, previous studies showed only a modest increase in Cu susceptibility of Mtb in the absence of the copper-binding metallothionein MymT (12) and the putative inner membrane CtpV (11) and no or only a minor virulence defect in mice or guinea pigs. By contrast, the survival of the ΔmctB mutant ML256 in the lungs of guinea pigs was strongly impaired as compared with WT Mtb, resulting in a 1,000-and 100-fold reduced bacterial burden in lungs and lymph nodes (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, previous studies showed only a modest increase in Cu susceptibility of Mtb in the absence of the copper-binding metallothionein MymT (12) and the putative inner membrane CtpV (11) and no or only a minor virulence defect in mice or guinea pigs. By contrast, the survival of the ΔmctB mutant ML256 in the lungs of guinea pigs was strongly impaired as compared with WT Mtb, resulting in a 1,000-and 100-fold reduced bacterial burden in lungs and lymph nodes (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…The ctpV gene (rv0969) is part of a Cu-induced operon controlled by the transcriptional regulator CsoR (10) and likely encodes a Cu-specific inner membrane efflux pump (9,10). However, the ctpV mutant did not show a clear virulence defect in mice and guinea pigs (11). Further, Mtb produces the metallothionine MymT, a small protein that binds up to six Cu(I) ions and partially protects Mtb from Cu toxicity (12).…”
mentioning
confidence: 99%
“…The gene ctpV, encoding an exporter, is induced during infection of macrophages (Graham & Clark-Curtiss, 1999) and in the Wayne hypoxia model (Muttucumaru et al, 2004) and is required for copper efflux as well as for detoxification and full virulence of Mtb during copper stress (Ward et al, 2010). Studies have suggested that copper homeostasis mechanisms may play a role in the outcome of bacterial infections (Ward et al, 2010). Like ctpV, ctpG is also copper inducible (Rowland & Niederweis, 2012), but it is predicted to function in the efflux of zinc (Argüello et al, 2007).…”
Section: Transportmentioning
confidence: 99%
“…Transcription of this operon is induced by copper, consistent with the predicted role of CtpV in excretion of excess copper under free-living conditions. Additionally, expression of ctpV is induced during infection of mouse lungs, suggesting a role of the copper-ATPase in virulence (Ward et al, 2010).…”
Section: Myc Tuberculosismentioning
confidence: 99%